Confabulations in Cases of Dementia: Atypical Early Sign of Alzheimer’s Disease or Misleading Feature in Dementia Diagnosis? - Belli, Elisabetta; Nicoletti, Valentina; Radicchi, Claudia; Bonaccorsi, Joyce; Cintoli, Simona; Ceravolo, Roberto; Tognoni, Gloria (Frontiers in Psychology, 2020)
Confabulations, also known as false memories, have been associated with various diseases involving mainly the frontal areas, such as Wernicke-Korsakoff syndrome or frontal epilepsy. The neuropsychological dysfunctions underlying mechanisms of confabulation are not well known. We describe two patients with memory impairment and confabulations at the onset speculating about neuropsychological correlates of confabulations and self-awareness. Both patients, a 77-year-old woman and a 57-years-old man, exhibited confabulations as first symptom of cognitive decline. She later developed memory impairment without awareness of her memory deficits and her cognitive and imaging profile suggested an amnesic Mild Cognitive Impairment due to Alzheimer’s disease (AD). Unlike her, he developed a prevalent involvement of frontal functions despite a clear consciousness of his cognitive deficits. However, the clinical diagnostic hypothesis of behavioural variant of Frontotemporal dementia was not supported by imaging findings which suggested AD. Both patients underwent neuropsychological evaluation including the Confabulation Battery. Despite the exact anatomical correlation of confabulations is still not defined, imaging data showed by our patients is consistent with recent theories according to which at the origin of confabulatory tendency in AD there is an impairment of the connections between crucial hubs in frontal and medio-temporal areas, mainly involving the right hemisphere. Besides, it would be reasonable to hypothesize that self-awareness and confabulations should not be considered as necessarily associated dimensions.